2014
DOI: 10.1016/j.clinph.2013.12.111
|View full text |Cite
|
Sign up to set email alerts
|

Emotion perception and electrophysiological correlates in Huntington’s disease

Abstract: Objective This study aimed to characterise, emotion perception deficits in symptomatic Huntington's disease (HD) via the use of event-related potentials (ERPs). Methods ERP data were recorded during a computerised facial expression task in 11 HD participants and 11 matched controls. Expression (scrambled, neutral, happy, angry, disgust) classification accuracy and intensity were assessed. Relationships between ERP indices and clinical disease characteristics were also examined. Results Accuracy was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
3
14
0
Order By: Relevance
“…Secondly, certain alterations in visual processing appear to occur as a correlate of processing emotional stimuli, which may be related to alterations in scanning behavior. That is, investigations into the neural correlates of facial emotion recognition in HD, using EEG (Croft et al, 2014), fMRI (Dogan et al, 2013), and MRI (Harrington et al, 2014), indicated an association between altered visual processing and emotion recognition. Nevertheless, a single study in HD that measured eye-movements during emotion processing did not find evidence for altered visual scanning (Van Asselen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, certain alterations in visual processing appear to occur as a correlate of processing emotional stimuli, which may be related to alterations in scanning behavior. That is, investigations into the neural correlates of facial emotion recognition in HD, using EEG (Croft et al, 2014), fMRI (Dogan et al, 2013), and MRI (Harrington et al, 2014), indicated an association between altered visual processing and emotion recognition. Nevertheless, a single study in HD that measured eye-movements during emotion processing did not find evidence for altered visual scanning (Van Asselen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies were conducted on a single gender, such as those investigating women's emotions during motherhood and parental status [133,134,164] and a study of men [215]. Some studies targeted a specific type of subject, such as healthy people or patients, to investigate and observe the differences in emotions between two different groups, such as control and healthy groups in [76,107,135], groups of women and men in [46,97,177], young adults versus older adults in [87,216], or children versus adults in [126,143].…”
Section: Mahnobmentioning
confidence: 99%
“…For example, increased activity in superior and middle frontal gyri in premanifest HD during emotion recognition coupled with intact behavioral performance could reflect compensation processes (Novak et al, 2012). Other factors that complicate interpretation include abnormal eye movements and visual processing defects (Croft, McKernan, Gray, Churchyard, & Georgiou-Karistianis, 2014). Inclusion of a control task may help to address the incidental effect of motor or perceptual impairments.…”
mentioning
confidence: 99%